Functional outcomes reporting using an adjusted outcomes index for mechanical thrombectomy in anterior cerebral artery occlusions – A case series - Fana, Michael; Sanmugananthan, Praveen; Santangelo, Giulia; Kole, Max; Chebl, Alex B.; Marin, Horia (Interdisciplinary neurosurgery : Advanced techniques and case management, 2025)
•Stent-retrievers with luminal diameter range 3–6 mm are optimal for ACA MT.•The 90-day mRS score may not accurately reflect functional outcomes for ACA MT.•Baseline-adjusted NIHSS with ≥41 % score decrease may challenge utility of 90-day mRS. The decision to intervene with mechanical thrombectomy (MT) for anterior cerebral artery (ACA) strokes is often made based on anticipated long-term functional outcomes using modified Rankin scores (mRS) which is primarily based on ambulatory status. Here, we review our single-center experience with ACA MT and evaluate the utility of various functional outcomes reporting. A case series of 15 patients undergone MT for ACA stroke using the Solitaire or Trevo stent-retrievers was completed. The data retrieved included patient demographics, initial National Institute of Health Stroke Scale (NIHSS), thrombolysis in cerebral infarction (TICI) scores and number of passes, post-procedure 24-hour NIHSS, intra-operative or post-operative complications, discharge NIHSS and mRS, and 90-day mRS. There were 87 % favorable ACA TICI scores (i.e. 2B/C and 3) and 80 % first pass recanalization rate. The Solitaire 4 mm stent-retriever was employed in the majority of cases (60 %). No procedural complications were noted in 73 % of cases and no hemorrhagic conversion in 87 % of cases. 90-day mRS scores of 0–2 were noted in 26 % of patients. Using an adjusted outcomes index, 80 % of patients had favorable outcomes based on the 24-hour baseline-adjusted NIHSS score decrease of ≥41 %. Our preliminary findings here highlight successful radiographic and favorable functional outcomes using the Solitaire and Trevo stent-retrievers (3–6 mm luminal diameter) for ACA MT when reporting with the adjusted outcomes index as compared to the 90-day mRS score. Further studies comparing these outcomes reporting metrics with a larger sample size will be needed to further elucidate this notable difference.